2023
DOI: 10.1038/s41598-023-32106-5
|View full text |Cite
|
Sign up to set email alerts
|

Design of topology optimized compliant legs for bio-inspired quadruped robots

Abstract: Robotic legs are an important component of the quadruped robot for achieving different motion gaits. Although the conventional rigid-link-based legs can generally perform robust motions, they still have the issues with poor sealing when operating in complex and liquid terrains. To cope with this problem, fully compliant legs with monolithic structure have been introduced in recent years to improve the system compactness and structural compliance of quadruped robots. In this article, we present a topology-optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Previous studies on EPA-based hopping robots have demonstrated the benefits of combining passive and active impedance, showcasing improvements in efficiency, robustness, and controller generalization [28][29][30][31]. This approach leverages the body as a computational resource, incorporating intelligence into the mechanical design, particularly through the use of soft materials, termed "mechanical intelligence" [32][33][34][35][36]. Moreover, incorporating PAMs into the actuation system facilitates their seamless integration into various configurations within the robot structure, such as mono-articular or bi-articular arrangements [31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on EPA-based hopping robots have demonstrated the benefits of combining passive and active impedance, showcasing improvements in efficiency, robustness, and controller generalization [28][29][30][31]. This approach leverages the body as a computational resource, incorporating intelligence into the mechanical design, particularly through the use of soft materials, termed "mechanical intelligence" [32][33][34][35][36]. Moreover, incorporating PAMs into the actuation system facilitates their seamless integration into various configurations within the robot structure, such as mono-articular or bi-articular arrangements [31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on EPA-based hopping robots have demonstrated the benefits of combining passive and active impedance, showcasing improvements in efficiency, robustness, and controller generalization [ 28 , 29 , 30 , 31 ]. This approach leverages the body as a computational resource, incorporating intelligence into the mechanical design, particularly through the use of soft materials, termed “mechanical intelligence” [ 32 , 33 , 34 , 35 , 36 ]. Moreover, incorporating PAMs into the actuation system facilitates their seamless integration into various configurations within the robot structure, such as mono-articular or bi-articular arrangements [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, problems in real-world applications are rarely linear or noise-free, making it challenging for these classical techniques to deliver optimal solutions consistently. Nature-inspired optimization methods have gained prominence due to their ability to address these limitations [ 11 , 12 , 13 ]. Algorithms like Genetic Algorithms, Particle Swarm Optimization, Ant Colony Optimization, and Simulated Annealing draw inspiration from biological, ecological, and physical processes.…”
Section: Introductionmentioning
confidence: 99%